Human adipose CD34+CD90+ stem cells and collagen scaffold constructs grafted in vivo fabricate loose connective and adipose tissues1. Issue 5 (14th March 2013) - Ferraro, Giuseppe A.; De Francesco, Francesco; Nicoletti, Gianfranco; Paino, Francesca; Desiderio, Vincenzo; Tirino, Virginia; D'Andrea, Francesco
Abstract Stem cell based therapies for the repair and regeneration of various tissues are of great interest for a high number of diseases. Adult stem cells, instead, are more available, abundant and harvested with minimally invasive procedures. In particular, mesenchymal stem cells (MSCs) are multi‐potent progenitors, able to differentiate into bone, cartilage, and adipose tissues. Human adult adipose tissue seems to be the most abundant source of MSCs and, due to its easy accessibility; it is able to give a considerable amount of stem cells. In this study, we selected MSCs co‐expressing CD34 and CD90 from adipose tissue. This stem cell population displayed higher proliferative capacity than CD34−CD90− cells and was able to differentiate in vitro into adipocytes (PPARγ+ and adiponectin+) and endothelial cells (CD31+VEGF+Flk1+). In addition, in methylcellulose without VEGF, it formed a vascular network. The aim of this study was to investigate differentiation potential of human adipose CD34+/CD90+ stem cells loaded onto commercial collagen sponges already used in clinical practice (Gingistat) both in vitro and in vivo. The results of this study clearly demonstrate that human adult adipose and loose connective tissues can be obtained in vivo, highlighting that CD34+/CD90 ASCs are extremely useful for regenerative medicine. J. Cell. Biochem. 114: 1039–1049, 2013. © 2012 Wiley Periodicals, Inc.